Sunlight-activated graphene-heterostructure transparent cathodes: enabling high-performance n-graphene/p-Si Schottky junction photovoltaics1. Issue 7 (1st July 2015) - Ho, Po-Hsun; Lee, Wei-Chen; Liou, Yi-Ting; Chiu, Ya-Ping; Shih, Yi-Siang; Chen, Chun-Chi; Su, Pao-Yun; Li, Min-Ken; Chen, Hsuen-Li; Liang, Chi-Te; Chen, Chun-Wei
<x xml:space="preserve">Abstract</x> A record-high efficiency (>10%) was achieved for an n-graphene/p-Si Schottky junction solar cell by using the "sunlight-activated" graphene/TiOx transparent cathode.